Relationship between dietary protein and amino acid intake and handgrip strength in Korean adults: data from the 2014–2019 Korea National Health and Nutrition Examination Survey - Hyunji Ham; Sumin Kim; Kyungho Ha (Nutrition Journal)
Abstract Background Sarcopenia contributes to an increased risk of falls and fractures, and reduced mobility, and mortality. Supplementation with dietary protein and amino acids has been suggested as a potential strategy to slow or prevent the associated loss of muscle mass and strength. However, most previous studies have focused on dietary protein or limited populations, such as older adults. Therefore, this study aimed to investigate the relationship between dietary protein and amino acid intake and handgrip strength (HG) in Korean adults. Methods This study used data from the 2014–2019 Korea National Health and Nutrition Examination Survey. A total of 18,565 adults who participated in a 1-day 24-hour recall method were included. Protein intake was calculated as a percentage of total energy intake from food sources (animal and plant). Amino acid intake (g/day), including essential amino acids (EAAs), branched-chain amino acids (BCAAs), and non essential amino acids (NEAAs), was assessed using a database expanded based on amino acid composition databases constructed by national institutions. Low HG was diagnosed based on the 2019 guidelines of the Asian Working Group on Sarcopenia. Results In the fully adjusted model, total and plant protein intakes were positively associated with HG levels (kg) (β = 0.04 and 0.07 per 1% increase, respectively; p < 0.05 for both). Participants aged ≥ 65 years in the highest NEAA intake group had a 42% lower risk of low HG compared to those in the lowest intake group (odds ratio 0.58; 95% confidence interval 0.35–0.97; p for trend = 0.1026). A lower risk of HG was observed in older participants whose plant protein intake ranged from 8 to 10% of energy, compared to those consuming less than 7%. However, no association was found when intake exceeded 10% of energy. Conclusions These findings suggest that a high intake of NEAAs and a moderately high intake of plant protein may be associated with a lower risk of low HG among Korean older adults. Further prospective studies are needed to explore the effects of protein and amino acid intake on muscle mass and strength.